2000
DOI: 10.1074/jbc.275.8.5888
|View full text |Cite
|
Sign up to set email alerts
|

A Minimized Human Integrin α5β1 That Retains Ligand Recognition

Abstract: Two isolated recombinant fragments from human integrin, and induces a specific conformational adaptation of the fibronectin ligand. A two-site model for RGD binding to both ␣ and ␤ integrin components is inferred from our data using low molecular weight RGD mimetics. Integrins (IN)1 are a family of structurally and functionally related adhesion receptors that participate in cell-cell and cellextracellular matrix (EM) interactions (1). All integrins are heterodimers of non-covalently associated ␣ and ␤ subunits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
48
1
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 73 publications
3
48
1
1
Order By: Relevance
“…The InterPro database indicated that both RbmC and Bap1 contain one possible calcium-binding site, two and one FG-GAP domains, respectively, and one galactose mutarotase-like domain. The FG-GAP domains are found in the extracellular N-terminal region of the integrin ␣-chain, which has been reported to be involved in ligand recognition and binding with proteins in the extracellular matrix or surface proteins on other cells (5,43). The galactose mutarotase-like domains, on the other hand, are described by the Structural Classification of Proteins database as probable carbohydrate-binding domains in enzymes acting on sugars.…”
Section: Resultsmentioning
confidence: 99%
“…The InterPro database indicated that both RbmC and Bap1 contain one possible calcium-binding site, two and one FG-GAP domains, respectively, and one galactose mutarotase-like domain. The FG-GAP domains are found in the extracellular N-terminal region of the integrin ␣-chain, which has been reported to be involved in ligand recognition and binding with proteins in the extracellular matrix or surface proteins on other cells (5,43). The galactose mutarotase-like domains, on the other hand, are described by the Structural Classification of Proteins database as probable carbohydrate-binding domains in enzymes acting on sugars.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, a novel cation binding site, termed the MIDAS motif, was identified in the crystal structures within the I-domains of several ␣ subunits and was found to be central to ligand binding functions of these I-domains (10, 58 -61). Evidence for the existence of MIDAS motifs in the I-domains of ␤ 1 , ␤ 2 , and ␤ 3 has also been developed (14,16,17,47,51,62,64). Although the I-domains of the ␣ and ␤ subunits are predicted to have similar MIDAS folds, their cation binding properties appear to differ significantly.…”
Section: Discussionmentioning
confidence: 99%
“…This region of ␤ 1 (residues 121-329) forms a heterodimer with ␣ 5 (160 -448) (47), and the same region of ␤ 3 (residues 111-318) complexes with ␣ IIb (1-233) (51 V 275 GSDNH between human and avian ␤ 3 was found to change the specificity of ␣ IIb /␤ 3 association (51). Taken together, these data strongly implicate this central region of the ␤ subunits in either heterodimer formation or in controlling the pairing specificity between the ␣ and ␤ subunits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early studies showed that PHSRN binds to the R 5 subunit (20,23) while RGD binds to both the R 5 and 1 subunits (45)(46)(47)(48). It was also demonstrated that PHSRN is not required for cell adhesion to FN and FN matrix assembly when integrins are in the activation state (23,49).…”
Section: Discussionmentioning
confidence: 99%